Occupational stress: imbalance in the Nursing professional exercise (Research, Society and Development, 2020)
This study proposes the analysis of materials already published on the following subjects: The importance of the nursing profession that is gaining more space in the health area, Occupational stress in the Exercise of the Nursing Profession, and Burnort Syndrome (a more severe form of stress when not treated early); in order to identify stressors in the workplace and seek measures to prevent disease or interference early. The information for the elaboration of the research was obtained through the search of publications of electronic journals with database in Scielo, Google academic and Virtual Health Library (VHL) in which were found several triggering factors of the disease and concluded that occupational stress it is a health problem caused mainly by work, its non-treatment can evolve to Burnout Syndrome and one of the main preventive measures is the knowledge of the nurse on the subject.